Characteristics of patients with coronary artery disease and type 2 diabetes mellitus undergoing elective percutaneous coronary intervention - Anastasiya G. Neeshpapa; Victoria N. Karetnikova (КардиоСоматика)
BACKGROUND: Patients with coronary artery disease (CAD) and type 2 diabetes mellitus (T2DM) represent a distinct group at high cardiovascular risk. Up-to-date information on their management in real-world clinical practice may help identify gaps in care.